Зубовский институт: (Пост)фольклор переходного времени [The Zubov Institute: (Post)folklore of the Time of Troubles] - Khazdan, Evgenia (Slavica Revalensia, 2016)
The article describes the lore of the Russian Institute of Art History (Zubov Institute) in the period from July 2013 to April 2014, i.e in the beginning of a series of highly unpopular measures imposed on this institution by the Ministry of Culture. It introduces some texts mocking the new director and her aides, and tells the story of how the Russian Institute of Art History functioned during the transitional period.